3D Information Technologies in Cultural Heritage Preservation and Popularisation - Milosz, Marek; Kęsik, Jacek (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue of the journal Applied Sciences presents recent advances and developments in the use of digital 3D technologies to protect and preserve cultural heritage. While most of the articles focus on aspects of 3D scanning, modeling, and presenting in VR of cultural heritage objects from buildings to small artifacts and clothing, part of the issue is devoted to 3D sound utilization in the cultural heritage field.